Public Service Narratives in Local Government Instagram Caption in Indonesia - Annada Nasyaya; Januar Eko Aryansah; Krisna Murti (Department of Public Administration, 2026)
Digital transformation has encouraged local governments in Indonesia to use Instagram as a platform for public communication and service representation. This study examines how public service is narrated in the Instagram captions of provincial governments and how these narratives reflect the principles of good governance: transparency, accountability, participation, and accessibility. Using Corpus-Assisted Discourse Studies (CADS), this research combines corpus linguistics and Critical Discourse Analysis (CDA). Data were collected from the official Instagram accounts of six Indonesian provincial governments during the first six months after the inauguration of regional leaders in 2025. The corpus was analyzed through keyword, collocation, and concordance techniques using AntConc, followed by discourse interpretation based on Fairclough’s framework. The findings show that Instagram captions are dominated by leadership representation, bureaucratic legitimacy, and the promotion of government programs. Keywords related to governors, government institutions, and development appear more frequently than words associated with transparency, accountability, and public participation. Collocation and concordance analyses indicate that citizens are mostly positioned as beneficiaries rather than active partners in governance. This study concludes that digital transformation has increased government visibility but has not fully shifted bureaucratic communication toward a participatory and citizen-centered model.